Expression pattern of thymosin beta 4 in the adult human liver - S. Nemolato; P. Van Eyken; T. Cabras; F. Cau; M.U. Fanari; A. Locci; D. Fanni; C.L.P. Gerosa; I. Messana; M. Castagnola; G. Faa (European Journal of Histochemistry, 2011)
Thymosin beta-4 (Tβ4) is a member of beta-thymosins, a family of small peptides involved in polymerization of G-actin, and in many critical biological processes including apoptosis, cell migration, angiogenesis, and fibrosis. Previous studies in the newborn liver did not reveal any significant reactivity for Tβ4 during the intrauterine life. The aim of the present study was to investigate by immunohistochemistry Tβ4 expression in the adult normal liver. Thirty-five human liver samples, including 11 needle liver biopsies and 24 liver specimens obtained at autopsy, in which no pathological change was detected at the histological examination, were immunostained utilizing an anti-Tβ4 commercial antibody. Tβ4 was detected in the hepatocytes of all adult normal livers examined. A zonation of Tβ4 expression was evident in the vast majority of cases. Immunostaining was preferentially detected in zone 3, while a minor degree of reactivity was detected in periportal hepatocytes (zone 1). At higher power, Tβ4-reactive granules appeared mainly localized at the biliary pole of hepatocytes. In cases with a strong immunostaining, even perinuclear areas and the sinusoidal pole of hepatocytes appeared interested by immunoreactivity for Tβ4. The current work first evidences a strong diffuse expression of Tβ4 in the adult human liver, and adds hepatocytes to the list of human cells able to synthesize large amounts of Tβ4 in adulthood. Moreover, Tβ4 should be added to the liver proteins characterized by a zonate expression pattern, in a descending gradient from the terminal vein to the periportal areas of the liver acinus. Identifying the intimate role played by this peptide intracellularly and extracellularly, in physiology and in different liver diseases, is a major challenge for future research focusing on Tβ4.